2019
DOI: 10.1101/601641
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unequal interactions between alcohol and nicotine co-consumption: Suppression and enhancement of concurrent drug intake

Abstract: Rationale Alcohol and nicotine addiction are prevalent conditions that co-occur. Despite the prevalence of co-use, factors that influence the suppression and enhancement of concurrent alcohol and nicotine intake are largely unknown.Objectives Our goals were to assess how nicotine abstinence and availability influenced concurrent alcohol consumption, and to determine the impact of quinine adulteration of alcohol on aversion resistant alcohol consumption and concurrent nicotine consumption.Methods Male and femal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 53 publications
(22 reference statements)
2
3
0
Order By: Relevance
“…Our results agree with previous findings showing no sex differences in basic aversion sensitivity for quinine [7880] or shock [81]. We also find that aversion-resistance across doses of quinine was not different between females and males, agreeing with previous studies showing sex-similar quinine sensitivity in alcohol under home cage bottle-drinking conditions ([80,82,83] but see [75]). However, other studies have found that females can be more aversion-resistant, including under operant responding for alcohol [79] and shock-resistance in a place preference model [81].…”
Section: Discussionsupporting
confidence: 93%
“…Our results agree with previous findings showing no sex differences in basic aversion sensitivity for quinine [7880] or shock [81]. We also find that aversion-resistance across doses of quinine was not different between females and males, agreeing with previous studies showing sex-similar quinine sensitivity in alcohol under home cage bottle-drinking conditions ([80,82,83] but see [75]). However, other studies have found that females can be more aversion-resistant, including under operant responding for alcohol [79] and shock-resistance in a place preference model [81].…”
Section: Discussionsupporting
confidence: 93%
“…We also found that CIE vapor inhalation selectively impacted aversion-resistant drinking in male, but not female rats. We found no impact of sex independently of CIE vapor inhalation, consistent with some prior reports (DeBaker et al, 2020;Randall et al, 2017;Sneddon et al, 2018), but not others (Fulenwider et al, 2019;Sneddon et al, 2020). Prior reports examining the impact of CIE vapor inhalation on aversion-resistant drinking have not, to our knowledge, included female subjects (Vendruscolo et al, 2012), though differences in other measures of compulsive alcohol seeking have been reported (Xie et al, 2019).…”
Section: Sex Differences In Ethanol Consumption and The Effects Of Ci...supporting
confidence: 90%
“…Greater aversion resistance in female versus male mice has also been demonstrated for oral fentanyl consumption in the home cage, but not the operant chamber (Monroe & Radke, 2020). It is important to note that not all studies have found sex differences in aversion resistance (Bauer, McVey, & Boehm, 2021; DeBaker, Moen, Robinson, Wickman, & Lee, 2020; Sneddon et al., 2019), further demonstrating the importance of the behavioral paradigm in revealing female vulnerability to addictive behavior. See Table 1 for more information.…”
Section: Female Vulnerability In Drug Self‐administration Studiesmentioning
confidence: 99%